2021
DOI: 10.48550/arxiv.2111.00358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey on the Robustness of Feature Importance and Counterfactual Explanations

Abstract: There exist several methods that aim to address the crucial task of understanding the behaviour of AI/ML models. Arguably, the most popular among them are local explanations that focus on investigating model behaviour for individual instances. Several methods have been proposed for local analysis, but relatively lesser effort has gone into understanding if the explanations are robust and accurately reflect the behaviour of underlying models. In this work, we present a survey of the works that analysed the robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In [22], the focus is on analytical trade-offs between validity and cost. We also refer to [23] for a survey on the robustness of both feature-based attributions and counterfactuals.…”
Section: Methodsmentioning
confidence: 99%
“…In [22], the focus is on analytical trade-offs between validity and cost. We also refer to [23] for a survey on the robustness of both feature-based attributions and counterfactuals.…”
Section: Methodsmentioning
confidence: 99%
“…Various local explanation methods however have been criticized for not being robust (Artelt et al, 2021;Hancox-Li, 2020;Mishra et al, 2021) or that they might fail to explain the global behavior of complex models (Slack et al, 2021).…”
Section: Counterfactual Explanationsmentioning
confidence: 99%
“…Evaluate consistency among explanations provided by multiple methods at global/local stage is a straightforward and inexpensive approach to get insights into model stability and robustness, but results must be handled cautiously. Empirical and theoretical analysis demonstrated that the majority of popular feature importance and counterfactual explanation methods are non-robust (Mishra et al 2021). In particular, most works focused on XAI methods that are specific to DNN models.…”
Section: Stability and Robustnessmentioning
confidence: 99%